Unilateral temporal muscle hypertrophy in a child with bruxism: a case report with literature review - Muhammad Khadafi (Universitas Muhammadiyah Sumatera Utara, 2021)
Hypertrophies in masticatory muscles are usually seen with variations in the masseter, temporalis and pterygoid muscles and are usually bilaterally. The most common presentation of these cases being bilateral whether isolated or combined. However, unilateral and isolated temporal muscle hypertrophy is still an extremely rare condition. The exact etiology has not been identified but theoretically, parafunctional movements like bruxism have been considered.